The decoupling between hemodynamic parameters and neural activity implies a complex origin of spontaneous brain oscillations - Li, Ming; He, Lihua; Zhang, Zhuo; Li, Zhen; Zhu, Xuan; Jiao, Chong; Hu, Dewen (Frontiers in Computational Neuroscience, 2023)
Spontaneous low-frequency oscillations play a key role in brain activity. However, the underlying mechanism and origin of low-frequency oscillations remain under debate. Here, optical imaging and an electrophysiological recording system were combined to investigate spontaneous oscillations in the hemodynamic parameters and neuronal activity of mice in different states (awake and anesthetized). The spectrum of local field potential (LFP) signals was significantly changed by Nω-nitro-L-arginine methyl ester (L-NAME), which was further corroborated by the increase in energy and spatial synchronization. The important finding was that L-NAME triggered regular oscillations in both LFP signals and hemodynamic signals. Notably, the frequency peak of hemodynamic signals can be different from that of LFP oscillations in awake mice. A model of the neurovascular system was proposed to interpret this mismatch of peak frequencies, supporting the view that spontaneous low-frequency oscillations arise from multiple sources.